2022
DOI: 10.1007/s11440-022-01588-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and biodeterioration behaviours of a clayey soil strengthened with combined carrageenan and casein

Abstract: In the last decade, biopolymers have been used as organic soil binders in ground improvement and earthen construction material modification. Although biopolymer-treated soils have substantially enhanced mechanical strength, the deformation characteristics under external loads and material durability (e.g. biodeterioration due to microbial activity) have not yet been fully understood, which limits the in situ practical application of the biopolymer-based soil treatment technology. This study investigated the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 72 publications
(146 reference statements)
1
14
0
Order By: Relevance
“…It was reported that the theoretical CO2 emission rate is around 0.7 kg/kg for the most common Ordinary Portland Cement (OPC) in China (Nie et al, 2022). Within the few decades, efforts have been paid to promote the reduction of CO2 emissions in construction field by using low carbon materials such as geopolymer (Farooq et al, 2021), biocement (Xiao et al, 2022a) and biopolymer (Ni et al, 2022). Geopolymer works as the cementitious composite in concrete based on the polycondensation of aluminosilicate under alkaline conditions, which has the potential of around 35% CO2 emission reduction than OPC (Farooq et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that the theoretical CO2 emission rate is around 0.7 kg/kg for the most common Ordinary Portland Cement (OPC) in China (Nie et al, 2022). Within the few decades, efforts have been paid to promote the reduction of CO2 emissions in construction field by using low carbon materials such as geopolymer (Farooq et al, 2021), biocement (Xiao et al, 2022a) and biopolymer (Ni et al, 2022). Geopolymer works as the cementitious composite in concrete based on the polycondensation of aluminosilicate under alkaline conditions, which has the potential of around 35% CO2 emission reduction than OPC (Farooq et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of extraction and fermentation techniques in chemical and biological engineering, the cost of producing biopolymer decreases hugely (Chang et al, 2020), making its application in the geotechnical field feasible and costacceptable. The representative natural-based biopolymers for soil stabilization can be classified as microorganism-based biopolymers such as xanthan gum and gellan gum, plant-based biopolymers such as guar gum and carrageenan gum, and animal-based biopolymers such as chitosan and casein (Ni et al, 2022). These biopolymers may have different physical and chemical properties due to their differences in molecular structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, a new type of soil reinforcement material biopolymer, which is environmentally friendly and quick-acting, has been gaining an increasing opportunity to be used in the field of geotechnical engineering [1][2][3][4][5][6]. Biopolymer-based soil treatment technology is used to improve the geotechnical properties of soils by adding plant or microbial secretions, as well as some artificially synthesized organic polymers to the soil [7].…”
Section: Introductionmentioning
confidence: 99%